A bizarre highly vascular tumor with alarming presentation: a diagnostic dilemma - Buckshee, Kamal; Harsh, Rastogi; Deepshikha, Arora; B. Tanya, Rohatgi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
An exceedingly rare, highly vascular tumor with atypical and alarming presentation posed diagnostic and management challenges. A 29 years old lady, complained of abdominal and pelvic pain, nausea, vomiting and repeated spells of fainting attacks following the jumping episode (2-3 times). Emergency admission and investigations at United States of America (USA) revealed a large, complex, highly vascular, irregular mass displaying finger like projections, filling the lower abdomen, pelvis and large amount of intra peritoneal bleed. A provisional diagnosis of arteriovenous malformation (AVM), arteriovenous fistula (AVF), and rupture/leak was made. Uterine artery angiography (UAA), preoperative embolization and possibility of hysterectomy as a life saving measure were suggested, to which the couple declined and got discharged. To save uterus and fertility they presented to us for second opinion and further management. Angiography, magnetic resonance imaging (MRI) and preoperative uterine artery embolization were done followed by exploratory laparotomy which revealed hemoperitoneum and a large weird looking vascular tumor (a veil of sea weeds/dark purple nodules of various sizes resembling cotyledons of placenta). Intra-operative tissue analysis (frozen section) suggested benign pathology. Mass was removed completely and fertility sparing surgery was undertaken. Histopathological diagnosis was cotyledonoid dissecting leiomyoma (CDL). No recurrence/metastasis has been observed on follow up of 5 years.